Spatial distribution of gambling: two indexes in support of the reduction of health inequalities. (30th September 2020) - Papineau, E; Robitaille, E; Prisca Samba, C; Lemétayer, F; Kestens, Y; Raynault, M-F
Abstract: Background: Many studies have showed that disadvantaged areas residents have greater access to gambling sites and are more affected by gambling. Our research proposes an innovative method to characterize gambling environments in Quebec and addresses social inequality with respect to gambling exposure. Methods: This cross-sectional ecological study was carried out in 3 stages: a Gambling Exposure Index (GEI) was built and is composed of 3 dimensions: spatial accessibility to gambling sites, density of gambling places, and relative risk associated with the types of game. The two-step floating catchment area (2SFCA) method was used to combine these dimensions into an overall GEI index. Data was retrieved from a geocoded directory of gambling sites and commercial databases. The relative risk of games is expressed by prevalence rates for those specific games in a Quebec population prevalence survey. A Vulnerability to Gambling Index (VGI) was produced based on 6 socio-economic proxies of problem gambling from the 2016 Canadian census, which were weighted and aggregated at the dissemination area (DA) level. Spatial and descriptive statistical analyses were conducted to explore the relationship between VGI and GEI, and to identify highly exposed and vulnerable areas. Results: Our analyzes reveal significant associations between the GEI and the VGI in 2 599 out of 13 420 Quebec DAs (p < 0.05). Sectors with a high GEI show an average distance to the closest gambling sites of 2.8 km compared with 13.5 km for more advantaged sectors. Conclusions: The interactive online mapping of the two indexes and statistical analysis of the results are beneficial to the professionals working in several fields such as risk monitoring, management of zoning, licensing and gambling distribution, prevention and treatment services. The method and the associated tools can be adapted to address the problem of increased accessibility to other unhealthy products in vulnerable neighborhoods. Key messages: Two innovative ecological indexes show that increased accessibility to gambling correlates with a higher vulnerability to gambling in many Quebec regions. The online interactive map on gambling exposure and vulnerability provides reliable criteria to municipal, regional and governmental bodies for a safer distribution of gambling offer.